CGIAR System Framework, 2016 - Amended 01 October 2024 - CGIAR System Management Office (CGIAR, 2024)
This Framework was approved by the CGIAR System’s Funders and Centers on 17 June 2016, and was last amended with effect from 1 October 2024.